KESIAPAN GEDUNG LIPPO PLAZA SIDOARJO DALAM MENGHADAPI BENCANA KEBAKARAN - Noor Aulady, Mohamad Ferdaus; Nuciferani, Felicia Tri; Zaharudin, Emir Ardiyan (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2023)
The high risk/impact of fire is the main reason for disaster preparedness to be carried out. the frequency of building fires that occurred in Indonesia in 2016 reached 100,000 incidents, with a total death toll ranging from 200-1000 people. Based on this incident, it is hoped that the community will pay more attention to the importance of preparedness in anticipating fire hazards so that casualties can be minimized. This study aims to determine the degree of visitor preparedness and the extent to which preparedness indicators influence, including disaster knowledge, emergency planning skills, early warning, and resource mobilization for preparedness. as well as the readiness of the existing fire protection system at the Lippo Plaza Sidoarjo shopping center. This study used a quantitative method with an analytic survey design and a cross sectional approach. The sampling technique was accidental sampling, with a total sample of 75 respondents. While data analysis consisted of univariate analysis based on the results of the average value of the questionnaire, multivariate analysis using the path analysis method, and fire protection system analysis using the checklist method. Based on the research results it is known that the average value of visitor preparedness is 63%. The emergency planning capability indicator has the greatest direct influence on preparedness of 11.97%, while the disaster knowledge indicator has the least direct influence on preparedness of 5.42%. The results of observations regarding the fire protection system for the Lippo Plaza Sidoarjo building, the overall results of the fire protection system including planning and the type of equipment used are included in the good category.